MATHEMATICAL MODEL OF NATURAL GAS HUMIDITY ANALYZER - Bilinsky, Yosif; Onushko, Vasyl (Scientific Works of Vinnytsia National Technical University, 2015)
There had been suggested the mathematical model for two-channel gas humidity analyzer, as well as methodology for determination of specific molar absorptivity indexes of natural gas and water vapor. There had been carried out the experimental tests to check the received results of relative humidity.